Factors Associated with Emotional Intelligence of Children Aged 3-6 Years - Asmarawanti, Asmarawanti; Arifin, Rani Fitriani; Purnairawan, Yosep (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: This study aimed to determine the factors associated with the emotional intelligence of children aged 3-6 years. Methods: This type of research uses correlation with a cross-sectional approach. The population of this study was 140 people, with a sample of 140 parents with children aged 3-6 years in Wangunreja Village, Sukabumi Regency, using a total sampling technique. The answer value scale refers to the Likert scale. Data collection techniques using questionnaires. Data were analyzed using univariate analysis with frequency distribution and percentage of each category. Bivariate analysis using chi-square. Results: The results showed that most respondents were 20-35 years old, 108 people (77.1%), had a high school education, 48 people (34.2%), worked, 75 people (53.5%), had female children, 78 people (55.7%), had the first child, 58 people (41.4%), had children aged three years, 55 people (39.3%), had a democratic parenting style, 49 people (35.1%), and had children with high emotional intelligence, 56 people (40.0%). There is a relationship between maternal age, child gender, and parenting style with the emotional intelligence of children aged 3-6 years (p-value <0.05). There is no relationship between maternal education and emotional intelligence of children aged 3-6 years (p-value >0.05). Conclusion: There is a relationship between maternal age, child gender, and parenting style with emotional intelligence of children aged 3-6 years and no relationship between maternal education and emotional intelligence of children aged 3-6 years.